Integrating the Least Developed Countries into the World Trading System : The Current Impact of EU Preferences under Everything but Arms - Brenton, Paul (World Bank, Washington, DC, 2014)
Trade preferences are a key element in industrial countries' efforts to assist the integration of least developed countries (LDCs) into the world economy. Brenton provides an initial evaluation of the impact of the European Union's recently introduced "Everything but Arms" (EBA) initiative on the products currently exported by the LDCs. He shows that the changes introduced by the EBA initiative in 2001 are relatively minor for currently exported products, primarily because over 99 percent of EU imports from the LDCs are in products which the EU had already liberalized, and the complete removal of barriers to the key remaining products-rice, sugar, and bananas-has been delayed. Brenton looks at the role EU preferences to LDCs in general have been playing and could play in assisting the integration of the LDCs. He shows that there is considerable variation across countries in the potential impact that EU preferences can have given current export structures. There is a group of LDCs for whom EU trade preferences on existing exports are not significant since these exports are mainly of products where the most-favored-nation duty is zero. Export diversification is the key issue for these countries. For other LDCs, EU preferences have the potential to provide a more substantial impact on trade. However, the author shows that only 50 percent of EU imports from non-ACP (Africa, Caribbean, and Pacific) LDCs which are eligible actually request preferential access to the EU. The prime suspect for this low level of use are the rules of origin, both the restrictiveness of the requirements on sufficient processing and the costs and difficulties of providing the necessary documentation. More simple rules of origin are likely to enhance the impact of EU trade preferences in terms of improving market access and in stimulating diversification toward a broader range of exports.